High-strength, high-toughness and corrosion-resistant heat-conducting composite material for flow battery and preparation method of heat-conducting composite material

In the composite materials for flow batteries, carbon fiber and graphene form fish bone structure through technical means such as flow orientation and shear rate, which solves the problems of low thermal conductivity and insufficient corrosion resistance of composite materials, and achieves efficient thermal conductivity , comprehensive improvement of excellent mechanics and corrosion resistance.

CN119391062AActive Publication Date: 2025-02-07SHANGHAI UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411611025.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-07
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

Existing composite materials have low thermal conductivity and insufficient corrosion resistance in liquid flow batteries, making it difficult to meet high performance requirements. Moreover, the interfacial compatibility between carbon fiber and graphene in polymer matrix is ​​poor, resulting in uneven dispersion of fillers and increasing interfacial thermal resistance. .

Method used

Through flow orientation, shear rate, interface compatibility and dispersion control, during the melt extrusion process, carbon fiber and graphene form a fish bone-like structure along the flow direction. Carbon fibers provide mechanical support as the main skeleton, and graphene sheets The layers are arranged parallel to both sides of the carbon fiber to form a scale-distributed thermal and electrical path.

Benefits of technology

It significantly improves the thermal conductivity, mechanical strength and chemical corrosion resistance of composite materials, reduces the interface thermal resistance, and meets the comprehensive performance requirements of energy storage systems such as flow batteries for materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391062A_ABST
    Figure CN119391062A_ABST
Patent Text Reader

Abstract

The invention discloses a heat-conducting composite material for a high-strength, high-toughness and corrosion-resistant flow battery and a preparation method of the heat-conducting composite material. The method comprises the following steps: S1, preparing modified carbon fibers; s2, preparing a modified carbon fiber functional master batch; and S3, preparing the high-strength, high-toughness and corrosion-resistant heat-conducting composite material for the flow battery. The heat-conducting composite material prepared by the invention has a fishbone-like microstructure, and is constructed through mutual interpenetration of carbon fibers and graphene sheet layers, so that covalent bond combination of a multi-phase interface of the material is improved, the interface thermal resistance is remarkably reduced, and the heat-conducting property of the material is favorably improved. The method is simple in technological process, controllable in cost and suitable for industrial large-scale production; the prepared composite material has excellent mechanical properties and chemical corrosion resistance, can meet various high-performance requirements of the flow battery on the material, can be widely applied to manufacturing of energy storage systems requiring high thermal conductivity and corrosion resistance such as the flow battery, and meets various composite high-performance requirements of the system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of high-performance composite materials, and in particular to a thermally conductive composite material for a high-strength, high-toughness, corrosion-resistant liquid flow battery and a preparation method thereof. Background Art

[0002] With the widespread application of energy storage systems and electronic devices, the demand for thermally conductive and corrosion-resistant composite materials is increasing. In energy storage systems, especially new energy devices such as flow batteries, thermal conductivity and corrosion resistance are key factors affecting system stability and life. The high temperature and corrosive electrolyte in flow batteries place stringent requirements on materials. Traditional polyethylene-based composite materials are difficult to meet such high-performance requirements due to their low thermal conductivity and insufficient corrosion resistance. In order to achieve efficient heat dissipation and long-term use, a composite material with high thermal conductivity, corrosion resistance and high strength and toughness is urgently needed to adapt to harsh working environments. However, how to effectively improve thermal conductivity and enhance corrosion resistance in a polymer matrix is ​​still one of the difficulties in the field of composite material technology.

[0003] Carbon fiber is often used to enhance the mechanical properties of polymer composites due to its high strength, high modulus and corrosion resistance; graphene can significantly improve the thermal conductivity of composite materials due to its excellent thermal conductivity. However, in the polymer matrix, the interface compatibility of carbon fiber and graphene is poor and they are prone to agglomeration, which leads to uneven dispersion of fillers in the matrix, increases the thermal resistance of the interface, and weakens the overall thermal conductivity. How to effectively disperse and synergize carbon fiber and graphene to give full play to the enhanced properties of both is the current technical bottleneck in the field of thermal conductive composite materials.

[0004] At present, composite materials mostly adopt randomly distributed microstructures, which have great limitations in filler dispersion and interface bonding. Due to the lack of order in the arrangement of carbon fiber and graphene in the matrix, filler agglomeration and high interface thermal resistance are usually caused, which weakens the overall thermal conductivity of the material. In addition, it is difficult for the randomly distributed filler structure to achieve the ideal enhancement effect in terms of mechanical properties, and it is impossible to give full play to the synergistic effect of carbon fiber and graphene. Traditional processes are difficult to accurately control the dispersion and interface bonding of fillers, resulting in limited improvements in thermal conductivity, mechanical properties and corrosion resistance of composite materials. Summary of the invention

[0005] In view of the above-mentioned deficiencies, the present invention aims to provide a method for preparing a high-strength, high-toughness, corrosion-resistant thermally conductive composite material for liquid flow batteries. During the melt extrusion process, the carbon fiber and graphene form a fishbone-like structure along the flow direction through flow orientation, shear rate, interface compatibility and dispersion control, wherein the carbon fiber serves as the main skeleton to provide mechanical support, and the graphene sheets are arranged in parallel along both sides of the carbon fiber to form a scale-like distribution of thermal and electrical conductive paths, thereby making the prepared thermally conductive composite material have high thermal conductivity, mechanical properties and chemical corrosion resistance.

[0006] The technical solution adopted by the present invention to achieve the above-mentioned purpose is: A method for preparing a thermally conductive composite material for a high-strength, high-toughness, corrosion-resistant liquid flow battery, characterized in that it comprises the following steps: S1. Preparation of modified carbon fiber After the continuous carbon fiber tow is cleaned by nitrogen purge, it is placed in an ultraviolet treatment chamber with a set oxygen concentration and irradiated for a set time to introduce oxygen-containing functional groups such as hydroxyl, carboxyl and carbonyl on the surface of the carbon fiber through ultraviolet-induced atomic oxygen surface activation, and then cut to a fixed length to prepare a modified carbon fiber; S2. Preparation of modified carbon fiber functional masterbatch The modified carbon fiber and graphene are dispersed in a peroxide compound non-proton solution of a set concentration according to a set ratio, taken out after being immersed in the solution, heated and dried, and the peroxide compound is introduced on the surface of the carbon fiber and graphene; the treated carbon fiber and graphene are then immersed in an ethylene monomer solution, the initiator is activated by high temperature and high pressure, and the ethylene monomer is induced to undergo free radical polymerization on the surface of the carbon fiber and graphene for a set time and then discharged to prepare a modified carbon fiber functional masterbatch; S3. Preparation of high-strength, high-toughness, corrosion-resistant thermally conductive composite materials for flow batteries The modified carbon fiber functional masterbatch in step S2 is introduced into the polyethylene resin in proportion, and the shear rate and melt strength are controlled during the in-situ reaction and melt extrusion molding process to form a fishbone-like support structure in which fibers and graphene sheets are interspersed. The multiphase interface of the composite material is covalently bonded to reduce the interfacial thermal resistance of the material, thereby preparing a thermally conductive composite material for liquid flow batteries having high thermal conductivity, mechanical properties and chemical corrosion resistance.

[0007] The carbon fiber tow is a 1K-48K polyacrylonitrile, asphalt-based, viscose-based or carbon fiber prepared by carbonization treatment of waste fibers, with a diameter of 7-20 μm and a carbon content of ≥99wt%.

[0008] The wavelength range of the ultraviolet light source is 180-190 nm, the oxygen concentration is 21%-99%, the set irradiation time is 10-60 min, and the cutting length of the modified carbon fiber is 1-5 mm.

[0009] The mass ratio of carbon fiber to graphene in step S2 is 1:1-10; the peroxide compound is one or more combinations of benzoyl peroxide, diisopropylbenzene peroxide, di-tert-butyl peroxide, azobisisobutylonitrile, and cumene peroxide; the aprotic solution is mainly one or more combinations of n-hexane, cyclohexane, petroleum ether, ethyl acetate, ethyl butyrate, benzene, toluene, and xylene.

[0010] In step S2, the concentration of the aprotic solution of the peroxide compound is set to 1-20 mg / mL, the high temperature is 200° C.-300° C., the high pressure is 1-3 MPa, and the polymerization time is 30-120 min.

[0011] The melt extrusion molding process parameters in step S3 include: heating temperature of 180-210° C., screw speed of 300-500 r / min, melt strength of 0.1-0.3 N, and shear rate of 300-800 s-1.

[0012] The ratio in step S3 is: 1 to 30 parts by mass of modified carbon fiber functional masterbatch and 70 to 99 parts by mass of polyethylene resin.

[0013] A high-strength, high-toughness, corrosion-resistant thermally conductive composite material for liquid flow batteries, which is prepared by the aforementioned method; the carbon fiber and graphene in the composite material form a fishbone-like structure along the flow direction, wherein the carbon fiber serves as the main skeleton to provide mechanical support, and the graphene sheets are arranged in parallel along both sides of the carbon fiber to form a scale-like distribution of thermal and electrical conductive paths, thereby constructing a microscopic skeleton of a fishbone-like structure in the polymer matrix, and through the arrangement of the carbon fiber and graphene, an efficient thermal conductive channel is formed to reduce the interface thermal resistance.

[0014] The high-strength, high-toughness, corrosion-resistant thermal conductive composite material for liquid flow batteries and the preparation method thereof provided by the present invention have the following beneficial effects: 1. The present invention constructs a fishbone-like micro-skeleton in the polymer matrix through the coordinated design of the preparation process and components, proportions and raw material structures, improves the interface bonding force and thermal conduction efficiency between fillers, and significantly enhances the thermal conductivity, mechanical strength and corrosion resistance of the composite material. Through the reasonable arrangement of carbon fiber and graphene, an efficient heat conduction channel is formed, the interface thermal resistance is reduced, and the thermal conduction efficiency of the material is greatly improved, which can meet the high-performance requirements of various composites such as large-scale energy storage systems.

[0015] 2. The fishbone-like microstructure constructed by the present invention is mainly formed by controlling the flow orientation, shear rate, interface compatibility and dispersion of carbon fiber and graphene along the flow direction during the melt extrusion process, wherein the carbon fiber serves as the main skeleton to provide mechanical support, and the graphene sheets are arranged in parallel along both sides of the carbon fiber to form a scale-like distribution of thermal and electrical conductive paths, thereby making the prepared thermally conductive composite material have high thermal conductivity, mechanical properties and chemical corrosion resistance.

[0016] 3. The present invention uses an in-situ reactive polymerization process to modify the surface of carbon fiber, realizes the uniform distribution of graphene on the surface of carbon fiber, and utilizes melt extrusion molding technology to form a stable fishbone-like structure of carbon fiber and graphene sheets in the matrix, forming a through heat conduction path in multiple directions. Through the microscopic design of the fishbone-like structure, the interface contact area between fillers is increased, and the interface thermal resistance is significantly reduced, so that the composite material has excellent chemical corrosion resistance and high strength and toughness while meeting the thermal conductivity requirements, meeting the comprehensive performance requirements of energy storage systems such as flow batteries for materials.

[0017] 4. The process flow of the present invention is simple, the cost is controllable, and it is suitable for large-scale industrial production. It is expected to be promoted and applied in high-performance demanding fields such as large-scale energy storage, electrical and electronic engineering, and thermal management.

[0018] The above is an overview of the technical solution of the invention. The present invention will be further described below in conjunction with specific implementation methods. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a SEM picture of the modified carbon fiber used to prepare the composite material according to the embodiment of the present invention; Figure 2 This is a SEM picture of a modified carbon fiber functional masterbatch for preparing a composite material according to an embodiment of the present invention; Figure 3 This is a SEM image of the thermally conductive composite material prepared in an embodiment of the present invention; Figure 4 It is a schematic diagram of the three-dimensional structure of a fishbone-like heat conduction path in a composite material prepared according to an embodiment of the present invention. DETAILED DESCRIPTION

[0020] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined purpose, the specific implementation methods of the present invention are described in detail below in combination with preferred embodiments.

[0021] Basic Example

[0022] See attached Figure 1-4 The method for preparing the high-strength, high-toughness, corrosion-resistant thermally conductive composite material for liquid flow batteries provided by the present invention comprises the following steps: Step S1: preparing modified carbon fiber After the continuous carbon fiber tow is cleaned by nitrogen purge, it is placed in an ultraviolet treatment chamber with a set oxygen concentration for a set time, and oxygen-containing functional groups such as hydroxyl, carboxyl and carbonyl are introduced on the surface of the carbon fiber through ultraviolet-induced atomic oxygen surface activation. After being cut to a fixed length, the modified carbon fiber can be prepared; Step S2: preparing modified carbon fiber functional masterbatch The modified carbon fiber and graphene are dispersed in a non-proton solution of a peroxide compound at a set concentration according to a set ratio. After immersion in the solution, the peroxide compound is taken out and heated and dried to introduce the peroxide compound onto the surface of the carbon fiber and graphene. The treated carbon fiber and graphene are immersed in a solution of ethylene monomer, and the initiator is activated by high temperature and high pressure to induce free radical polymerization of ethylene monomer on the surface of the carbon fiber and graphene for a set time and discharge the material to prepare the modified carbon fiber functional masterbatch.

[0023] Step S3: preparing a high-strength, high-toughness, corrosion-resistant thermally conductive composite material for a flow battery The modified carbon fiber functional masterbatch in S2 is introduced into the polyethylene resin. By regulating the shear rate and melt strength during the in-situ reaction and melt extrusion molding process, a fishbone-like support structure with fibers and graphene sheets interspersed is formed. This is beneficial to achieve covalent bonding at the multiphase interface of the composite material and reduce the interfacial thermal resistance of the material. The prepared thermally conductive composite material has high thermal conductivity, mechanical properties and chemical corrosion resistance.

[0024] The carbon fiber tow is a 1K-48K polyacrylonitrile, asphalt-based, viscose-based or carbon fiber prepared by carbonization treatment of waste fibers, with a diameter of 7-20 μm and a carbon content of ≥99wt%.

[0025] The wavelength range of the ultraviolet light source is 180-190 nm, the oxygen concentration is 21%-99%, the irradiation time is 10-60 min, and the cutting length of the modified carbon fiber is 1-5 mm.

[0026] The mass ratio of the carbon fiber to the graphene is 1:1-10, the peroxide compound is mainly one or more combinations of benzoyl peroxide, diisopropylbenzene peroxide, di-tert-butyl peroxide, azobisisobutylonitrile, and cumene peroxide, the aprotic solution is mainly one or more combinations of n-hexane, cyclohexane, petroleum ether, ethyl acetate, ethyl butyrate, benzene, toluene, and xylene, the concentration is 1-20 mg / mL, the high temperature is 200° C.-300° C., the high pressure is 1-3 MPa, and the polymerization time is 30-120 min.

[0027] The melt extrusion molding process parameters include a heating temperature of 180-210°C, a screw speed of 300-500 r / min, a melt strength of 0.1-0.3 N, and a shear rate of 300-800 s -1 .

[0028] The modified carbon fiber functional masterbatch is 1 to 30 parts by mass; and the polyethylene is 70 to 99 parts by mass.

[0029] The fishbone-like structure is mainly achieved by controlling flow orientation, shear rate, interface compatibility and dispersion during melt extrusion, so that carbon fiber and graphene form a fishbone-like structure along the flow direction, wherein the carbon fiber serves as the main skeleton to provide mechanical support, while the graphene sheets are arranged in parallel along both sides of the carbon fiber to form a scale-like distribution of thermal and electrical conductive paths, thereby making the prepared thermally conductive composite material have high thermal conductivity, mechanical properties and chemical corrosion resistance.

[0030] A high-strength, high-toughness, corrosion-resistant thermally conductive composite material for liquid flow batteries is prepared by the aforementioned method. The carbon fiber and graphene in the composite material form a fishbone-like structure along the flow direction, wherein the carbon fiber serves as the main skeleton to provide mechanical support, and the graphene sheets are arranged in parallel along both sides of the carbon fiber to form a scale-like distribution of thermal and electrical conductive paths, thereby constructing a microscopic skeleton of a fishbone-like structure in the polymer matrix. Through the arrangement of carbon fiber and graphene, an efficient thermal conductive channel is formed to reduce the interface thermal resistance.

[0031] The following is a detailed description through four specific embodiments.

[0032] Example 1 See attached Figure 1-2 The method for preparing the high-strength, high-toughness, corrosion-resistant thermally conductive composite material for liquid flow batteries provided in an embodiment of the present invention comprises the following steps: S1. Preparation of modified carbon fibers A 12K polyacrylonitrile carbon fiber tow with a diameter of 7 μm was cleaned by nitrogen purge and then placed in a 180 nm ultraviolet treatment chamber with an oxygen concentration of 21% for 10 min. After cutting, a modified carbon fiber with a length of 1 mm was prepared. S2. Preparation of modified carbon fiber functional masterbatch The modified carbon fiber and graphene powder are dispersed in a 1 mg / mL benzoyl peroxide n-hexane solution at a ratio of 1:1, and after being immersed in the solution, they are taken out and heated and dried, and then immersed in an ethylene monomer solution, and free radical polymerization of polyethylene is carried out in a high temperature and high pressure environment (temperature is 200°C, pressure is 1MPa) for 30 minutes, and then the material is discharged to prepare a modified carbon fiber functional masterbatch; S3. Preparation of high-strength, high-toughness, corrosion-resistant thermally conductive composite materials for flow batteries The modified carbon fiber functional masterbatch prepared in step S2 is introduced into the polyethylene resin, and the heating temperature is set to 180-200°C, the screw speed is 300r / min, the melt strength is 0.1N, and the shear rate is 300s -1 High-strength, high-toughness, and corrosion-resistant thermal conductive composite pipes for liquid flow batteries are prepared by melt extrusion blending, with the mass of modified carbon fiber functional masterbatch accounting for 1% and the mass of polyethylene matrix accounting for 99%.

[0033] Figure 1 is the SEM picture of modified carbon fiber; Figure 1 It can be seen that the carbon fiber surface is full of grooves, which significantly improves the surface roughness and interface compatibility of the fiber.

[0034] Figure 2 is the SEM picture of modified carbon fiber functional masterbatch; Figure 2 It can be seen that the interpenetration between graphene sheets and carbon fibers can prevent the agglomeration of fillers, promote the dispersion of fillers in the resin matrix, and form a stable structure with multiphase interface bonding. The orderliness of the fishbone structure improves the uniformity of the material and helps the composite material maintain deformation stability under external stress.

[0035] Figure 3 This is a SEM image of a high-strength, high-toughness, corrosion-resistant thermally conductive composite material for flow batteries. Figure 3 It can be seen that the two-dimensional structure of graphene is laid flat around the carbon fiber to form parallel thermal conductivity paths, providing an in-plane thermal conductivity effect. The high thermal conductivity of graphene combined with carbon fiber constructs a multi-directional thermal conduction path, reduces the interfacial thermal resistance, and optimizes the overall thermal conduction of the material. The fishbone structure maximizes the characteristics of carbon fiber and graphene, combining the high strength of carbon fiber and the high thermal conductivity of graphene. The composite material prepared in this way has excellent thermal conductivity, mechanical strength and corrosion resistance.

[0036] Figure 4 Schematic diagram of the three-dimensional structure of the three-dimensional heat conduction path of the composite material according to the embodiment of the present invention. Figure 4 It can be seen that the modified carbon fibers and graphene sheets are distributed in an orderly manner, the interface compatibility between filler-filler and filler-resin is good, a continuous heat conduction path is formed in the three-dimensional direction, and the phonon transmission and scattering phenomenon is effectively suppressed, which is beneficial to the effective improvement of the thermal conductivity of the composite material.

[0037] The embodiments of the present invention construct a fishbone-like micro-skeleton in a polymer matrix through the coordinated design of the preparation process and components, proportions and raw material structures, thereby improving the interface bonding strength and thermal conduction efficiency between fillers, and significantly enhancing the thermal conductivity, mechanical strength and corrosion resistance of the composite material.

[0038] Example 2 The preparation method of the high-strength, high-toughness, corrosion-resistant thermally conductive composite material for liquid flow batteries provided by the present invention is substantially the same as that of Example 1, except that the preparation method comprises the following steps: S1. Preparation of modified carbon fibers A 10 μm diameter, 24K viscose-based carbon fiber tow was cleaned by nitrogen purge and then placed in a 182 nm wavelength ultraviolet treatment chamber with 40% oxygen concentration for 25 min. After cutting, a modified carbon fiber with a length of 3 mm was prepared. S2. Preparation of modified carbon fiber functional masterbatch The modified carbon fiber and graphene powder are dispersed in a 10 mg / mL di-tert-butyl peroxide n-hexane solution at a ratio of 1:3, and after being immersed in the solution, the mixture is taken out and heated and dried, and then immersed in an ethylene monomer solution. The polyethylene is subjected to free radical polymerization in a high temperature and high pressure environment (temperature is 220°C, pressure is 1.5MPa) for 20 minutes, and then the material is discharged to prepare a modified carbon fiber functional masterbatch; S3. Preparation of high-strength, high-toughness, corrosion-resistant thermally conductive composite materials for flow batteries The modified carbon fiber functional masterbatch prepared in step S2 is introduced into the polyethylene resin, and the heating temperature is set to 180-200°C, the screw speed is 350r / min, the melt strength is 0.2N, and the shear rate is 400s -1 High-strength, high-toughness, and corrosion-resistant thermal conductive composite pipes for liquid flow batteries are prepared by melt extrusion blending, with the modified carbon fiber functional masterbatch accounting for 10% by mass and the polyethylene matrix accounting for 90% by mass.

[0039] Example 3 The preparation method of the high-strength, high-toughness, corrosion-resistant thermally conductive composite material for liquid flow batteries provided by the present invention is substantially the same as that of Examples 1-2, except that the preparation method comprises the following steps: S1. Preparation of modified carbon fibers A 12 μm diameter, 36K pitch-based carbon fiber tow was cleaned by nitrogen purge and then placed in a 188 nm wavelength ultraviolet treatment chamber with 75% oxygen concentration for 40 min. After cutting, a modified carbon fiber with a length of 4 mm was prepared. S2. Preparation of modified carbon fiber functional masterbatch The modified carbon fiber and graphene powder are dispersed in a 15 mg / mL azobisisobutyronitrile benzene solution at a ratio of 1:8, and after being immersed in the solution, the mixture is taken out, heated and dried, and then immersed in an ethylene monomer solution. The polyethylene is subjected to free radical polymerization for 80 minutes in a high temperature and high pressure environment (temperature is 220°C, pressure is 2.5 MPa), and then the material is discharged to prepare a modified carbon fiber functional masterbatch; S3. Preparation of high-strength, high-toughness, corrosion-resistant thermally conductive composite materials for flow batteries The modified carbon fiber functional masterbatch prepared in step S2 is introduced into the polyethylene resin, and the heating temperature is set to 180-200°C, the screw speed is 400r / min, the melt strength is 0.2N, and the shear rate is 600s -1 High-strength, high-toughness, and corrosion-resistant thermal conductive composite pipes for liquid flow batteries are prepared by melt extrusion blending, with the modified carbon fiber functional masterbatch accounting for 20% by mass and the polyethylene matrix accounting for 80% by mass.

[0040] Example 4 The preparation method of the high-strength, high-toughness, corrosion-resistant thermally conductive composite material for liquid flow batteries provided by the present invention is substantially the same as that of Examples 1-3, except that the preparation method comprises the following steps: S1. Preparation of modified carbon fibers A 20 μm diameter, 48K pitch-based carbon fiber tow was cleaned by nitrogen purge and then placed in a 190 nm wavelength ultraviolet treatment chamber with an oxygen concentration of 99% for 60 min. After cutting, a modified carbon fiber with a length of 5 mm was prepared. S2. Preparation of modified carbon fiber functional masterbatch The modified carbon fiber and graphene powder are dispersed in a 20 mg / mL benzoyl peroxide n-hexane solution at a ratio of 1:10, and after being immersed in the solution, they are taken out and heated and dried, and then immersed in an ethylene monomer solution. The polyethylene is subjected to free radical polymerization in a high temperature and high pressure environment (temperature is 300°C, pressure is 3MPa) for 120 minutes, and then the material is discharged to prepare a modified carbon fiber functional masterbatch; S3. Preparation of high-strength, high-toughness, corrosion-resistant thermally conductive composite materials for flow batteries The modified carbon fiber functional masterbatch prepared in step S2 is introduced into the polyethylene resin, and the heating temperature is set to 190-210°C, the screw speed is 500r / min, the melt strength is 0.3N, and the shear rate is 800s -1 High-strength, high-toughness, and corrosion-resistant thermal conductive composite pipes for liquid flow batteries are prepared by melt extrusion blending, with the mass of modified carbon fiber functional masterbatch accounting for 30% and the mass of polyethylene matrix accounting for 70%.

[0041] Application Example 1 The thermal conductivity, tensile strength and corrosion resistance of the high-strength, high-toughness, corrosion-resistant and thermally conductive composite materials prepared in Examples 1 to 4 were tested, and the results are shown in the following table.

[0042]

[0043] It can be seen from the above table that the high-strength, high-toughness, corrosion-resistant and thermally conductive composite materials prepared in Examples 1 to 4 of the present invention, the preparation method and the composite material of the present invention, through flow orientation, shear rate, interface compatibility and dispersion control, make the carbon fiber and graphene form a fishbone-like structure along the flow direction, wherein the carbon fiber serves as the main skeleton to provide mechanical support, and the graphene sheets are arranged in parallel along both sides of the carbon fiber to form a scale-like distribution of thermal and electrical conductive paths, thereby making the prepared thermally conductive composite material have high thermal conductivity, mechanical properties and chemical corrosion resistance.

[0044] The composite material provided by the above-mentioned embodiments of the present invention has a fishbone-like microstructure constructed by the interpenetration of carbon fibers and graphene sheets, which improves the covalent bonding of the multiphase interface of the material, significantly reduces the interfacial thermal resistance, and helps to improve the thermal conductivity of the material. In addition, the composite material can simultaneously have excellent mechanical properties and chemical corrosion resistance, and can meet the performance requirements of liquid flow batteries for materials; the preparation process of the present invention is simple, the cost is controllable, and it is suitable for large-scale industrial production, which can meet the needs of high-performance technical fields such as large-scale energy storage, electrical and electronic engineering, and thermal management, and can be widely used in the manufacture of liquid flow batteries and other energy storage systems that require high thermal conductivity and corrosion resistance.

[0045] In addition, it should be specially noted that within the scope of the above-described invention, other implementation schemes obtained by selecting other preparation processes, components and their proportions can achieve the technical effects described in the invention, so they will not be listed one by one.

[0046] The above description is only a preferred embodiment of the present invention and does not limit the technical scope of the present invention. Therefore, technical features that are the same or similar to those of the above-mentioned embodiments of the present invention are within the protection scope of the present invention.

Claims

1. A method for preparing a thermally conductive composite material for a high-strength, high-toughness, corrosion-resistant liquid flow battery, characterized in that: The following steps are involved: S1. Preparation of modified carbon fiber After the continuous carbon fiber tow is cleaned by nitrogen purge, it is placed in an ultraviolet treatment chamber with a set oxygen concentration and irradiated for a set time to introduce oxygen-containing functional groups such as hydroxyl, carboxyl and carbonyl on the surface of the carbon fiber through ultraviolet-induced atomic oxygen surface activation, and then cut to a fixed length to prepare a modified carbon fiber; S2. Preparation of modified carbon fiber functional masterbatch The modified carbon fiber and graphene are dispersed in a peroxide compound non-proton solution of a set concentration according to a set ratio, taken out after being immersed in the solution, heated and dried, and the peroxide compound is introduced on the surface of the carbon fiber and graphene; the treated carbon fiber and graphene are then immersed in an ethylene monomer solution, the initiator is activated by high temperature and high pressure, and the ethylene monomer is induced to undergo free radical polymerization on the surface of the carbon fiber and graphene for a set time and then discharged to prepare a modified carbon fiber functional masterbatch; S3. Preparation of high-strength, high-toughness, corrosion-resistant thermally conductive composite materials for flow batteries The modified carbon fiber functional masterbatch in step S2 is introduced into the polyethylene resin in proportion, and the shear rate and melt strength are controlled during the in-situ reaction and melt extrusion molding process to form a fishbone-like support structure in which fibers and graphene sheets are interspersed. The multiphase interface of the composite material is covalently bonded to reduce the interfacial thermal resistance of the material, thereby preparing a thermally conductive composite material for liquid flow batteries having high thermal conductivity, mechanical properties and chemical corrosion resistance.

2. The method for preparing the thermally conductive composite material for high-strength, high-toughness, corrosion-resistant liquid flow battery according to claim 1, characterized in that: The carbon fiber tow is a 1K-48K polyacrylonitrile, asphalt-based, viscose-based or carbon fiber prepared by carbonization treatment of waste fibers, with a diameter of 7-20 μm and a carbon content of ≥99wt%.

3. The method for preparing the thermally conductive composite material for high-strength, high-toughness, corrosion-resistant liquid flow battery according to claim 1, characterized in that: The wavelength range of the ultraviolet light source is 180-190 nm, the oxygen concentration is 21%-99%, the set irradiation time is 10-60 min, and the cutting length of the modified carbon fiber is 1-5 mm.

4. The method for preparing the thermally conductive composite material for high-strength, high-toughness, corrosion-resistant liquid flow battery according to claim 1, characterized in that: The mass ratio of carbon fiber to graphene in step S2 is 1:1-10; the peroxide compound is one or more combinations of benzoyl peroxide, diisopropylbenzene peroxide, di-tert-butyl peroxide, azobisisobutylonitrile, and cumene peroxide; the aprotic solution is mainly one or more combinations of n-hexane, cyclohexane, petroleum ether, ethyl acetate, ethyl butyrate, benzene, toluene, and xylene.

5. The method for preparing the thermally conductive composite material for high-strength, high-toughness, corrosion-resistant liquid flow battery according to claim 1, characterized in that: In step S2, the concentration of the aprotic solution of the peroxide compound is set to 1-20 mg / mL, the high temperature is 200° C.-300° C., the high pressure is 1-3 MPa, and the polymerization time is 30-120 min.

6. The method for preparing the thermally conductive composite material for high-strength, high-toughness, corrosion-resistant liquid flow battery according to claim 1, characterized in that: The melt extrusion molding process parameters in step S3 include: heating temperature 180-210°C, screw speed 300-500r / min, melt strength 0.1-0.3N, shear rate 300-800s -1 .

7. The method for preparing the thermally conductive composite material for high-strength, high-toughness, corrosion-resistant liquid flow battery according to claim 1, characterized in that: The ratio in step S3 is: 1 to 30 parts by mass of modified carbon fiber functional masterbatch and 70 to 99 parts by mass of polyethylene resin.

8. A high-strength, high-toughness, corrosion-resistant thermally conductive composite material for a flow battery, characterized in that: It is prepared according to the method according to any one of claims 1 to 7.

9. The thermally conductive composite material for high-strength, high-toughness, corrosion-resistant liquid flow battery according to claim 8, characterized in that: The carbon fiber and graphene in this composite material form a fishbone-like structure along the flow direction, in which the carbon fiber serves as the main skeleton to provide mechanical support, and the graphene sheets are arranged in parallel along both sides of the carbon fiber to form a scale-like distribution of thermal and electrical conductive pathways. In this way, a fishbone-like microscopic skeleton is constructed in the polymer matrix. Through the arrangement of carbon fiber and graphene, an efficient thermal conductive channel is formed to reduce the interface thermal resistance.

Citation Information

Patent Citations

  • Polymer heat-conducting master batch as well as preparation method and application thereof

    CN111978615A

  • Modified carbon fiber reinforced resin-based composite material and preparation method thereof

    CN112661990A

  • High-strength composite material for new energy automobile and preparation method of high-strength composite material

    CN117050452A

  • Multifunctional modified co-carbonized carbon fiber composite material as well as preparation method and application thereof

    CN118580683A

  • High-thermal-conductivity reinforced polyphenylene sulfide composite material and preparation method therefor

    WO2022121547A1